2018
DOI: 10.1002/cem.3083
|View full text |Cite
|
Sign up to set email alerts
|

Moving window partial least squares after orthogonal signal correction as a coupling method for determination of uranium and thorium by ultrasound‐assisted emulsification microextraction

Abstract: This study, a fast, simple, and efficient ultrasound-assisted emulsification microextraction coupled with orthogonal signal correction-moving window partial least squares (OSC-MWPLS) was successfully used to preconcentration and simultaneous spectrophotometric determination of uranium and thorium in water samples. Response surface methodology based on a Box-Behnken design was used to optimize the extraction conditions. The analysis of variance and some statistical tests such as lack-of-fit and coefficient of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The effect of ultrasound was attributed to the efficient nucleation due to the cavitation microbubbles and intensive acoustic microstreaming as well [103]. Khorshidi et al applied 40 kHz ultrasound during the sample preparation step before spectrophotometric measurements were applied for the simultaneous determination of the concentrations of thorium and uranium in aqueous solutions [104]. The ultrasound-assisted emulsification micro-extraction approach consist in the rapid injection of small amounts of extracting solvents (carbon tetrachloride) in a sonicated aqueous media containing the elements of interest.…”
Section: Some Specific Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of ultrasound was attributed to the efficient nucleation due to the cavitation microbubbles and intensive acoustic microstreaming as well [103]. Khorshidi et al applied 40 kHz ultrasound during the sample preparation step before spectrophotometric measurements were applied for the simultaneous determination of the concentrations of thorium and uranium in aqueous solutions [104]. The ultrasound-assisted emulsification micro-extraction approach consist in the rapid injection of small amounts of extracting solvents (carbon tetrachloride) in a sonicated aqueous media containing the elements of interest.…”
Section: Some Specific Systemsmentioning
confidence: 99%
“…The as-formed cloudy solution is then centrifuged to concentrate the solvent before micrometric volumes are taken with a syringe prior to analyses. The authors reported several advantages including an acceleration of the formation of fine cloudy solutions with a minimum consumption of organic solvent, a reduced extraction time and a better extraction efficiency [104].…”
Section: Some Specific Systemsmentioning
confidence: 99%
“…Kennard-Stone (KS) was the most commonly employed sample set partitioning method. The Euclidean distance was used in the method as the reference condition for selection, whose calculation formula is as Equation (8). As can be seen, KS selects samples only based on spectral features without considering the influence of property variables [16] .…”
Section: Data Set Division By Spxymentioning
confidence: 99%
“…MWPLS builds a series of partial least squares (PLS) models in a window that moves over the whole spectral region and then locates useful spectral intervals in terms of the least complexity of PLS models reaching a desired error level. The main advantage of MWPLS is that the model is very stable against the interference from non-composition related factors [8] . However, in the process of such interval selection methods, some noises may be retained while some really useful information may be dropped, since they are always mixed together [9] .…”
Section: Introductionmentioning
confidence: 99%